HUBUNGAN KEPEMIMPINAN DAN PENGAWASAN TERHADAP KINERJA GURU DI MADRASAH TSANAWIYAH NEGERI 1 LUBUKLINGGAU - Ngatijo Ngatijo (Jurnal Media Ekonomi (JURMEK), 2017)
With the aim of the study is to determine the relationship of leadership to teacher performance in Madrasah Tsanawiyah Negeri 1 Lubuklkinggau. To find out the relationship of Supervision of Teacher performance in the Tsukawiyah Negeri 1 Lubuklinggau Madrasah. The results of this study used 45 respondents with data analysis techniques used using quantitative data. From the analysis of quantitative data there is the test result of t X1 test is a significant level of leadership variable (X1) on the performance variable (Y) which shows a calculated value of 4.209> Ttable = 1.68107 and X2 test is a significant level of supervision variable (X2) against performance variable (Y) which shows the value of Tcount equal to 5.606> Ttable = equal to 1.68107 and the F test is the leadership variable (X1) and supervision (X2) jointly on the performance variable (Y) which shows the calculated F value of 26.022> Ftable = equal to 3.22. R determination test is 0.744 and R Square is 0.553 so that the contribution of R variable (X1) and supervision (X2) to Performance (Y) is 0.744 x 100% = 74.4% and R Square is 0.553 x 100% = 55.3 The remaining% of the percentage is influenced by other variable factors outside the research.